Penerapan Metode Simple Additive Weighting (SAW) dan Tabel Keputusan pada Sistem Pendukung Keputusan Menentukan Tingkat Punishment Siswa Bermasalah - Riyadi Purwanto; Dwi Novia Prasetyanti; Ratih Hafsarah Maharrani; Lutfi Syafirullah (Infotekmesin, 2021)
One of the factors that affect the comfort of the learning process at school is students who violate school rules. To maintain school order, it is necessary to give punishment as stipulated in the school's decision. Decision Support System can be implemented as a media to support decision making in giving punishment to problematic students. In general, punishment for problematic students uses a point system according to the type of violation. However, the calculation and management process is still done conventionally which is prone to human error. Engineering punishment is very likely to occur due to the like and dislike factor. This of course causes the school's decision to be wrong. This study aims to make a Decision Support System application to determine the level of punishment for problematic students using the Simple Additive Weighting (SAW) method and the Decision Table. The weighting of violation points is based on three criteria, namely academic violations, aesthetic violations, and ethical violations. The results showed that the calculation of the weighted score of each type of student violation became more precise.